2018
DOI: 10.1097/sla.0000000000002440
|View full text |Cite
|
Sign up to set email alerts
|

Trends on Axillary Surgery in Nondistant Metastatic Breast Cancer Patients Treated Between 2011 and 2015

Abstract: This study shows a trend towards less extensive axillary surgery in Dutch cT1-T4N0M0 breast cancer patients; illustrated by an overall increase of sentinel lymph node biopsy and decrease in cALND. Despite this trend, particularly noticed in cT1-2N0 sentinel node-positive patients after publication of the ACOSOG-Z0011 and AMAROS trial, variations in patterns of care in axillary surgery are still present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 27 publications
5
47
0
Order By: Relevance
“…A Dutch population based study showed that between 2011 and 2015, the use of ALND following a positive SLNB significantly decreased from 24% to 6%. 15 Other single institutional investigations have confirmed similar findings with a significant change in clinical practice since the Z0011 study. [16][17][18][19][20] This is the first Australian of the Z0011 results in Australia has been slow following the publication of the Z0011 study.…”
Section: Discussionsupporting
confidence: 53%
“…A Dutch population based study showed that between 2011 and 2015, the use of ALND following a positive SLNB significantly decreased from 24% to 6%. 15 Other single institutional investigations have confirmed similar findings with a significant change in clinical practice since the Z0011 study. [16][17][18][19][20] This is the first Australian of the Z0011 results in Australia has been slow following the publication of the Z0011 study.…”
Section: Discussionsupporting
confidence: 53%
“…The number of patients aged 70 years or above seems lower in the present study than in previous studies. This might be explained by the fact that adjuvant chemotherapy is used less frequently in these older women in the Netherlands. Furthermore, postmastectomy IBR is used less frequently in this patient group in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Overall and positive lymph node yields were similar (NACT 13 and 3 vs ACT 14 and 4), suggesting that NACT rarely obviated ALND or downstaged the axilla. Other authors have also demonstrated high rates of persistent nodal involvement in ILC patients that ultimately made ALND unavoidable . In our study, 48.4% of patients who received NACT had T1 or T2 disease suggesting that in these cases, presentation with node‐positive disease may have driven the decision to pursue NACT.…”
Section: Discussionmentioning
confidence: 55%
“…But ILC is also nearly always hormone receptor (HR)‐positive, and previous studies have demonstrated that patients with low‐grade, HR‐positive (HR+) ILC have a poor response to NACT, experiencing lower rates of pathologic complete response (pCR) than patients with IDC . Concomitantly, NACT has historically been less successful in enabling breast conservation or omission of more extensive axillary surgery among ILC patients, who have higher rates of mastectomy and completion axillary lymph node dissection (ALND) than those with IDC . Nevertheless, similar criteria—including nodal involvement—are used to determine whether NACT should be administered in both histologic subtypes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation